THE MODERN PHYSICS PRACTICUM MODULE IS EQUIPPED WITH VIDEOS TO TRAIN HOTS - Wati, Listia; Bakri, Fauzi; Nasbey, Hadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2024)
Abstract The challenges of the Industrial Revolution 4.0 can be faced by improving the quality of education. One of them is by increasing Higher Order Thinking Skills (HOTS) in learning that can be trained in practicum activities. This study aims to produce a practicum module that is equipped with a practicum video with the stages of HOTS training. This development research uses the Dick and Carey Model which is limited to the ninth stage. The research was assessed using a feasibility instrument that included the content, use of language, practicum module components, graphical aspects, ease of use, technical requirements, didactic requirements, and implementation of the HOTS process. So material experts, media experts, and learning experts stated that the modern physics practicum module on the photoelectric effect and property material is suitable for training students' HOTS stages. Keywords: Modern Physics, Practicum Module, HOTS, Photoelectric Effect, Millikan, Planck's Constant. Abstrak Tantangan Revolusi Industri 4.0 dapat dihadapi dengan meningkatkan kualitas pendidikan. Salah satunya dengan meningkatkan Higher Order Thinking Skills (HOTS) dalam pembelajaran yang dapat dilatih dalam kegiatan praktikum. Penelitian ini bertujuan untuk menghasilkan Modul praktikum yang dilengkapi video praktikum dengan tahapan melatih HOTS. Penelitian pengembangan ini menggunakan Model Dick and Carey yang dibatasi hanya sampai pada tahap kesembilan. Penelitian dinilai menggunakan instrumen kelayakan yang mencakup penyajian materi, penggunaan bahasa, komponen modul praktikum, aspek kegrafikan, kemudahan penggunaan, syarat teknis, syarat didaktik, dan keterlaksanaan proses HOTS. Sehingga ahli materi, ahli media dan ahli pembelajaran menyatakan modul praktikum fisika modern pada materi efek fotolistrik dan milikan layak digunakan untuk melatih tahapan HOTS mahasiswa. Keywords: Fisika Modern, Modul Praktikum, HOTS, Efek Fotolistrik, Millikan, Konstanta Planck.